Pseudomonas spp. Enriched in Endophytic Community of Healthy Cotton Plants Inhibit Cotton Verticillium Wilt - Zeng, Qingchao; Man, Xiaowu; Dai, Yucheng; Liu, Haiyang (Frontiers in Microbiology, 2022)
The plant microbiome plays a fundamental role on plant growth and health. However, detailed information of plant endophytic microbiome during the infection period of pathogen is largely unknown. Here, we investigated the microbial community of healthy and diseased cotton plants and the root exudate profiles of susceptible and resistant cultivars utilizing high-throughput sequencing and metabolomics. The results showed that the pathogen infection reduced bacterial diversity and significantly affected the bacterial community composition. The microbiome assembly is shaped predominantly by cultivars. The endophytic microbiomes from infected plants showed greater complexity than the healthy plants in network analysis. It displayed that 76 compounds were significantly different in total, 18 compounds showed higher relative abundance in the resistant cultivars and 58 compounds in the susceptible cultivars. Pathway enrichment analysis showed that plant hormone signal transduction, biosynthesis of various secondary metabolites, biosynthesis and metabolism of amino acids were prominently altered pathways. We also demonstrate that plants inoculated with Pseudomonas sp. strains increased resistance to the cotton Verticillium wilt compared with the control plants in pot experiments. Overall, it showed that the pathogen infection affected the community composition and healthy plants enriched beneficial microbiome to defense plant disease. These findings significantly advance our understanding about the endophytic microbiome assembly under the pathogen infection and develop microbiome-based solutions for sustainable crop production systems.